Analisis Persediaan Beras Menggunakan Metode Economic Order Quantity Pada Bulog Divisi Regional Sulawesi Utara - Palepong, Jein Anastasya; Loho, Agnes Estephina; Montolalu, Maya Hendrietta (Sam Ratulangi University, 2024)
This research aims to determine the flow of rice procurement in the North Sulawesi Regional Division of Bulog, analyze the amount of rice inventory in the North Sulawesi Regional Division of Bulog and calculate rice inventory costs consisting of ordering costs and storage costs. This research was conducted from May to July 2023. The data used is secondary data. Secondary data is data that has been compiled in the form of written documents obtained from Bulog, North Sulawesi Regional Division and also obtained from the internet via Google Scholar in the form of books, journal articles and theses related to this research topic, namely Rice Supply Analysis Using the Economic Order Quantity Method. The results of the research show that the North Sulawesi Regional Division of Bulog has not provided optimal rice supplies. As for rice procurement, it is uncertain when it will be procured, the frequency of orders made at Bulog, North Sulawesi Regional Division during 2022 is 42 times, while in the EOQ calculation the order frequency is 35 times, this means that when using the EOQ method you can minimize ordering costs. Also, using the EOQ method, the maximum quantity available in the warehouse is known so that storage costs can be minimized.